The potential applications of T cell receptor (TCR)-like antibody in cervical cancer immunotherapy - Sylvia Annabel Dass; Rehasri Selva Rajan; Gee Jun Tye; Venugopal Balakrishnan (Taylor & Francis Group, 2021)
Cervical cancer is ranked as the fourth most common cancer in women worldwide. Monoclonal antibody has created a new dimension in the immunotherapy of many diseases, including cervical cancer. The antibody's ability to target various aspects of cervical cancer (oncoviruses, oncoproteins, and signaling pathways) delivers a promising future for efficient immunotherapy. Besides, technologies such as hybridoma and phage display provide a fundamental platform for monoclonal antibody generation and create the opportunity to generate novel antibody classes including, T cell receptor (TCR)-like antibody. In this review, the current immunotherapy strategies for cervical cancer are presented. We have also proposed a novel concept of T cell receptor (TCR)-like antibody and its potential applications for enhancing cervical cancer therapeutics. Finally, the possible challenges in TCR-like antibody application for cervical cancer therapeutics have been addressed, and strategies to overcome the challenges have been highlighted to maximize the therapeutic benefits.